Flavedo deshidratado de naranja (Citrus sinensis, variedad Valencia) y hojas de stevia (Stevia rebaudiana) para la elaboración de infusión cítrica - Pilco Aguirre, Gerson Jair (2020)
The orange (Citrus sinensis), is the citrus with the highest consumption in Ecuador; However, not all its parts are used, being discarded as waste. Among these parts is the flavedo, which contains a large number of beneficial properties; It could be used in by-products such as infusion whose market in the country is little known, representing an alternative for the consumer of hot, natural and healthy beverages. For this reason, in the present research work the suitable formulation of flavedo and Stevia, and the content in grams to obtain a citrus infusion, were determined. A completely randomized design (DCA) was used with a 3x3 factorial arrangement with 4 repetitions. Factor A was the flavedo: Stevia ratio, while factor B, the gram content of the infusion. The physical-chemical parameters evaluated were: humidity (%), pH, Brix degrees (%), acidity and total ash (%). The sensory evaluation were attributes of color, aroma, flavor and acceptability, in addition to the preference analysis where it was determined that the best treatment was T5 (95% flavedo, 5% Stevia in 2 grams) presenting values of 11.23% humidity, PH 5.18, Brix degrees 2.33%, acidity 0.00045% and total ash 3.48%. In the microbiological analysis of Aerobes, Molds and Yeasts, the values were within the parameters established in the NTE INEN 2392. In the economic analysis the cost of making the infusion was determined, resulting in a unit cost of $ 2.76 and a P.V.P. of $ 3.03 with a profit of 10%. Keywords: Orange peel, residue, added value, infusion, natural sweetener.